Cytochrome P450-mediated antiseizure medication interactions influence apoptosis, modulate the brain BAX/Bcl-XL ratio and aggravate mitochondrial stressors in human pharmacoresistant epilepsy - Ghosh, Chaitali; Westcott, Rosemary; Perucca, Emilio; Hossain, Mohammed; Bingaman, William; Najm, Imad (Frontiers in Pharmacology, 2022)
Polytherapy with antiseizure medications (ASMs) is often used to control seizures in patients suffering from epilepsy, where about 30% of patients are pharmacoresistant. While drug combinations are intended to be beneficial, the consequence of CYP-dependent drug interactions on apoptotic protein levels and mitochondrial function in the epileptic brain remains unclear. We examined the interactions of ASMs given prior to surgery in surgically resected brain tissues and of three ASMs (lacosamide, LCM; oxcarbazepine, OXC; levetiracetam LEV) in isolated brain cells from patients with drug-resistant epilepsy (n = 23). We divided the patients into groups – those who took combinations of NON-CYP+CYP substrate ASMs, NON-CYP+CYP inducer ASMs, CYP substrate+CYP substrate or CYP substrate+CYP inducer ASMs – to study the (a) pro- and anti-apoptotic protein levels and other apoptotic signaling proteins and levels of reactive oxygen species (reduced glutathione and lipid peroxidation) in brain tissues; (b) cytotoxicity at blood-brain barrier epileptic endothelial cells (EPI-ECs) and subsequent changes in mitochondrial membrane potential in normal neuronal cells, following treatment with LCM+OXC (CYP substrate+CYP inducer) or LCM+LEV (CYP substrate+NON-CYP-substrate) after blood-brain barrier penetration, and (c) apoptotic and mitochondrial protein targets in the cells, pre-and post-CYP3A4 inhibition by ketoconazole and drug treatments. We found an increased BAX (pro-apoptotic)/Bcl-XL (anti-apoptotic) protein ratio in epileptic brain tissue after treatment with CYP substrate+CYP substrate or inducer compared to NON-CYP+CYP substrate or inducer, and subsequently decreased glutathione and elevated lipid peroxidation levels. Further, increased cytotoxicity and Mito-ID levels, indicative of compromised mitochondrial membrane potential, were observed after treatment of LCM+OXC in combination compared to LCM+LEV or these ASMs alone in EPI-ECs, which was attenuated by pre-treatment of CYP inhibitor, ketoconazole. A combination of two CYP-mediated ASMs on EPI-ECs resulted in elevated caspase-3 and cytochrome c with decreased SIRT3 levels and activity, which was rescued by CYP inhibition. Together, the study highlights for the first time that pro- and anti-apoptotic proteins levels are dependent on ASM combinations in epilepsy, modulated via a CYP-mediated mechanism that controls free radicals, cytotoxicity and mitochondrial activity. These findings lead to a better understanding of future drug selection choices offsetting pharmacodynamic CYP-mediated interactions.